STUDENT PREPAREDNESS TOWARD MOUNT MERAPI ERUPTION IN SD NEGERI LENCOH IN SELO SUB DISTRICT - ratih puspita dewi (GeoEco, 2018)
Schools are one of vulnerable public places in case of disaster phenomenon. On the other side, school is a place where the children spend most of their time. It is possible that volcanic eruption occur while children study at school. Selo is one of the sub district of Boyolali district  that located on the north side of Mount Merapi, its location is quite close to the peak of Mount Merapi, it is makes Selo is prone to be affected by Mount Merapi eruption. The aim of this research was to determine the level of student preparedness toward Mount Merapi eruption in SD Negeri Lencoh. The method used in this research was descriptive qualitative. The population in this research were elementary students in the high grade with consideration that student in the high grade were better in understanding to fill out the questionnaire. The sampling technique was purposive sampling technique. The data collection technique was using questionnaire developed by LIPI. The result of this research  was the value of student preparedness level in SD Negeri Lencoh  which was 52.1 so it was conlude as less ready.